A Comparative Study of the Effects of Mint Tea Bag, Mint Cream, and Breast Milk on the Treatment of Cracked Nipple in the Lactation Period: A Randomized Clinical Trial Study - Tayebeh Gharakhani Bahar; Khodayar Oshvandi; Seyedeh Zahra Masoumi; Younes Mohammadi; Shirin Moradkhani; Farzin Firozian (Mashhad University of Medical Sciences, 2018)
Background: The results of the previous studies on the effects of mint on cracked nipple are contradictory. The purpose of the present study was to compare the effects of mint tea bag, mint cream and breast milk on the healing of cracked nipple during lactation. Methods: This study was a clinical trial with a control group , pre and post-test design conducted in health centers of Hamadan University of Medical Sciences, Hamadan, Iran from 2016 to 2017.Samples were divided into three groups (n=72 subjects in each group). Interventions were performed at least 4 times a day for 14 days after the start of treatment. Data were collected through the cracked nipple measuring checklist, the amount of wound and demographic questionnaire before the intervention and on 4, 8, and 14 days after the intervention. Data analysis was conducted using descriptive and inferential statistics in SPSS software (version 21). Results: There was a decreasing trend in the mean score of crack pain on days 0-14 in the groups of mint cream, mint tea, and breast milk after the intervention; however, there was a statistically significant difference in the breast milk group (P